Pollen viability-based heat susceptibility index (HSIpv): A useful selection criterion for heat-tolerant genotypes in wheat - Khan, Irum; Wu, Jiajie; Sajjad, Muhammad (Frontiers in Plant Science, 2022)
Terminal heat stress during reproductive stage in wheat (Triticum aestivum L.) causes pollen grains sterility and has a drastic impact on wheat crop production. Finding genotypes with high pollen viability under heat stress is crucial to cope with the impact of climate change through developing heat tolerant cultivars. To assess the effect of terminal heat stress on pollen viability in a panel of spring wheat genotypes (N = 200), RCBD (randomized complete block design)-field trials were conducted under normal and heat stress conditions for two consecutive years (2020-21 and 2021-22). Analysis of variance showed significant variation in genotypes, treatments and genotype*treatment interaction. Fifty and fourty six genotypes were categorized as heat tolerant (〖HSI〗_pv<0.5) in 1st and 2nd year, respectively. Twelve genotypes namely, Chenab-70, Pari-73, Pak-81, MH-21, Punjab-76, NIFA-Aman, NUWYT-63, Swabi-1, Nisnan-21, Frontana, Amin-2000 and Pirsabak-2004 were found as heat tolerant across the years. The violin plot displayed a trend of improvement in heat tolerance (〖HSI〗_pv<0.5) over the period of time in many modern wheat varieties. However, some modern wheat varieties released after 2001 such as Janbaz-09 (57%), Ghazi -2019 (57%), Sindhu-16 (43%) and Manthar-2003 (0%) had very low pollen viability under heat stress condition. The results of phenotypic coefficient of variance (PCV %), genotypic coefficient of variance (GCV %), broad sense heritability (h2bs) and genetic advance (GA) suggested major contribution of genetic factors in controlling pollen viability trait. Higher values h2bs and GA under heat stress condition suggested pollen viability as a heat tolerance trait controlled by additive genetic effects. Taken together, these results suggested pollen viability as a useful trait for selection in early generations under elevated temperatures. The genotypes identified as heat tolerant in both years can be used as useful genetic resources for breeding cultivars with higher pollen viability under elevated temperature conditions.